Synthesis of 3-octadecanoxypropyl 6-deoxy-6-sulfo-α-d-glucopyranoside (ODSG) as a lipase-resistant SQAP derivative. (15th November 2021) - Oshige, Masahiko; Kano, Koki; Shinada, Shunsuke; Kawaguchi, Akifumi; Uchida, Takato; Ishii, Nozomi; Horiuchi, Hiroaki; Sugawara, Fumio; Sakaguchi, Kengo; Matsuo, Ichiro; Katsura, Shinji
Graphical abstract: Abstract: Sulfoquynovosylacyl propanediol (SQAP; 1 ) has been developed as a radiosensitizer (anti-cancer agent) for solid tumors, but it was easily cleaved in vivo and had a problem of short residence time. We synthesized a novel compound of a SQAP derivative (3-octadecanoxypropyl 6-deoxy-6-sulfo-α-d -glucopyranoside: ODSG; 2 ) to solve these problems not easily cleaved by lipase. ODSG (2 ) cytotoxicity was investigated in vitro, resulting in low toxicity like SQAP (1 ).